2018
DOI: 10.3389/fphar.2018.00310
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine Receptor-Mediated Cardioprotection—Current Limitations and Future Directions

Abstract: Since the seminal reports of adenosine receptor-mediated cardioprotection in the early 1990s, there have been a multitude of such reports in various species and preparations. Original observations of the beneficial effects of A1 receptor agonists have been followed up with numerous reports also implicating A2A, A3, and most recently A2B, receptor agonists as cardioprotective agents. Although adenosine has been approved for clinical use in the United States for the treatment of supraventricular tachycardia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 74 publications
(102 reference statements)
1
21
0
1
Order By: Relevance
“…DeNinno et al (2003) reported that CP-608,039 35 is a highly A 3 AR selective and water-soluble agonist that was being evaluated for the prevention of perioperative myocardial ischemic injury. This follows numerous other reports showing that A 3 AR activation protects ischemic cardiomyocytes by preconditioning (Lasley, 2018).…”
Section: Ar Agonists For Clinical Developmentsupporting
confidence: 91%
See 1 more Smart Citation
“…DeNinno et al (2003) reported that CP-608,039 35 is a highly A 3 AR selective and water-soluble agonist that was being evaluated for the prevention of perioperative myocardial ischemic injury. This follows numerous other reports showing that A 3 AR activation protects ischemic cardiomyocytes by preconditioning (Lasley, 2018).…”
Section: Ar Agonists For Clinical Developmentsupporting
confidence: 91%
“…Anti-ischemic effect of A 1 AR agonists has been demonstrated in animal studies, but clinical successes are lacking, and more relevant clinical models are needed (Borea et al, 2016; Lasley, 2018).…”
Section: Ar Agonists For Clinical Developmentmentioning
confidence: 99%
“…The A 1 adenosine receptor (A 1 receptor) is a member of the ancient and ubiquitous adenosine receptor family that exerts complex regulatory functions in almost all tissues [ 3 , 4 , 5 ]. In the heart, the A 1 receptor mediates strong negative tropic effects including negative inotropy on the ventricle and, even more, on the atrium [ 6 ], as a component of the A 1 adenosinergic cardioprotection against ischemic/hypoxic stress [ 7 , 8 , 9 ]. Accordingly, in earlier studies, we aimed to assess the guinea pig atrial A 1 receptor reserve for the direct negative inotropic effect of several A 1 adenosine receptor agonists (the term direct means that experiments were conducted on atria lacking prior stimulation of contractility).…”
Section: Introductionmentioning
confidence: 99%
“…There is no "direct" evidence of the effect of A 2B AR on ventricular myocytes [178]; however, A 2B AR was shown to be required for A 1 AR-mediated cardioprotection [237]. In fact, adenosine levels during myocardial ischemia-reperfusion increase; therefore, low-affinity A 2B AR still has cardioprotective effects upon its activation [238].…”
Section: A 2b Ar In Cardiovascular Systemsmentioning
confidence: 99%
“…The role of cardioprotection by A 3 AR is enticing, enigmatic, and elusive [294]. Further clinical studies on cardioprotection induced by adenosine receptors need to establish the role of adenosine receptor agonists and antagonists in more clinically relevant models of myocardial ischemia [238].…”
Section: A 3 Ar In Cardiovascular Systemsmentioning
confidence: 99%